ROLE OF INSTITUTIONS IN ECONOMIC PERFORMANCE: AN EMPIRICAL STUDY ON INTERSTATE DIFFERENCES IN INDIAN STATES WITH REFERENCE TO JHARKHAND - Bimal C. Roy; Satyaki Sarkar; Nikhil Ranjan Mandal; Shashi Kant Pandey (European Scientific Journal, ESJ, 2014)
Existence of good institutions plays a very important role ineconomic performance. Though the term ‗institutions‘ covers a very widespectrum, this paper considers the legal aspect and extent of stateintervention as important components of institutions. However politicalinstitution has also been identified as an important factor that affectsindustrial growth and development. This paper empirically examines thesignificance of these factors in explaining variations in the per capita GDP ofthe Indian states and the extent of industrial development across them. Thestudy further uses the different indices of institutions for a comparativeanalysis among the states with reference to Jharkhand. Empirical findingssuggest that the extent of state intervention is significant in explaining thevariations in State Gross Domestic Product (SGDP) growth whereas legalinstitutions and political institutions both play a highly significant role inexplaining variations in the extent of industrial development across theIndian states.